EXAMINING THE EFFECT OF SAFETY LEADERSHIP TOWARDS SAFETY BEHAVIOUR AMONGST DOMESTIC COLLECTING WORKERS IN MALAYSIA (Journal of Technology and Operations Management, 2023)
Safety leadership is increasingly being championed as the preeminent strategy for mitigating workplace injuries through the improvement of safety behaviour. This reearch rigorously investigates the interplay between supervisory leadership and safety behaviour among employees involved in domestic waste collection. Drawing on the Social Exchange Theory (SET), the study elucidates how these three aspects of safety leadership function as pivotal mechanisms in fostering safer workplace behaviours within this high-risk sector. A quantitative cross-sectional survey, targeting 224 domestic waste collecting workers, was utilized, and data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). This results uncover the profound influence of safety leadership dimensions, namely safety coaching, safety concern, and safety monitoring, on safety behaviour among domestic waste collecting workers in Malaysia. This illuminates the vital role of multifaceted safety leadership in reducing workplace accidents and injuries. This study contributes valuable insights for industry practitioners, safety leaders, and policymakers, supporting their efforts to enhance safety standards in the waste collection sector. The findings pave the way for improved safety practices of the workforce within high-risk industries.